2019
DOI: 10.1021/acs.chemmater.9b02183
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphide Precursor for Low-Temperature Solution-Processed Fibrous Phosphorus Thin Films

Abstract: Crystalline red phosphorus has very recently emerged as a stable and cost-effective semiconductor material. However, despite its potentiality in electronics and optoelectronics, the widespread application of this material is still hampered by the limited synthetic route of the ampoule-based chemical vapor deposition that critically requires mineralizing agents. To address this issue, we report the chemical synthesis of soluble polyphosphide precursors that serve as inks for the solutionprocessed fabrication of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…17 Subsequently, the FP film was further studied by Ban et al; they reported an n-type semiconducting property and a remarkably strong photocurrent. 18 Our previous work revealed that an FP fiber has a rapid response time. 19 In addition, phosphorus is one of the most important elements in living organisms and so FP has a huge advantage in cell imaging.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Subsequently, the FP film was further studied by Ban et al; they reported an n-type semiconducting property and a remarkably strong photocurrent. 18 Our previous work revealed that an FP fiber has a rapid response time. 19 In addition, phosphorus is one of the most important elements in living organisms and so FP has a huge advantage in cell imaging.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Then, an FP film was synthesized by Smith et al on a silicon substrate, and the film showed carrier mobility of 308 cm 2 V –1 s –1 and an I on / I off ratio approaching 100 . Subsequently, the FP film was further studied by Ban et al; they reported an n-type semiconducting property and a remarkably strong photocurrent . Our previous work revealed that an FP fiber has a rapid response time .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the preparation of charged particles with soft stabilizers, such as ionic polymers or long-chain ionic molecules, at the surfaces of the particles is limited in most cases and requires an additional degree of control over the intermolecular interactions between the surface organic layers. ,,, Recently, significant advancement in the surface modification of NPs with molecular inorganic ions has been observed, which enables the synthesis of all-inorganic NPs with desired charges. , …”
Section: Introductionmentioning
confidence: 99%
“…[11,28] The sharp peaks around 353 and 368 cm À1 are related to phosphorus cage stretching vibrations in the tube-like substructure of cRP. [28,29] Compared with bulk, the Raman signals of cRP NRs are slightly shifted to high wavenumber direction (Supporting Information, Figure S5). The purity is evaluated by X-ray photoelectron spectroscopy (XPS) (Supporting Information, Figure S6) and energy-dispersive X-ray spectrometer (EDS) (Supporting Information, Figure S7).…”
mentioning
confidence: 99%